Training on The Utilization of Organic Waste Into Biobatteries as An Implementation of SDGs in The Merdeka Curriculum for Teachers - Herlina, Kartini; Abdurrahman, Abdurrahman; Fadiawati , Noor; Anggreini , Anggreini; Feredova, Kharinta Oxana; Putri , Mila Rosalia; Pratiwi, Dwi; Purnamasari, Adinda Putri (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2026)
The electricity crisis and the rise of organic waste are interconnected environmental issues that also affect education. The Merdeka Curriculum encourages contextual learning by exploring topics like renewable energy and waste management. However, limited practical tools hinder physics teachers in Bandarlampung from delivering SDG-related lessons effectively. This article aims to train physics teachers in creating and using organic waste-based biobatteries, such as those made from banana peels, as learning media. Biobatteries generate eco-friendly electricity and help students understand electrical concepts and sustainability. The training will include tests, discussions, and workshops conducted in an interactive manner. Expected outcomes include improved teacher competence, the creation of innovative practical tools, and publication.